Pancoast Tumor With Cardiac Metastases and Intracardiac Thrombosis - Shiavax J. Rao MD; Shaikh B. Iqbal DO; Usman Sagheer MD (SAGE Publishing, 2023)
Pancoast tumor is a rare and aggressive form of lung cancer; cardiac metastasis is very uncommon. We present a case of advanced Pancoast tumor, with extensive cardiac metastases and intracardiac thrombosis in a woman presenting with dyspnea, shoulder pain, and weight loss. A contrast-enhanced chest computed tomographic scan revealed an apical mass, metastatic thoracic nodes, and filling defects within both ventricles. Further imaging with cardiac magnetic resonance imaging revealed 2 left ventricular masses infiltrating into the myocardium suggestive of metastatic disease, and a multilobulated mass within the right ventricle suggestive of intracardiac thrombus. She was initiated on anticoagulation for intracardiac thrombosis. Surgical pathology of biopsied tissue samples was consistent with advanced metastatic lung adenocarcinoma. She was a poor candidate for surgical intervention. Given the patient's goals of care, she was ultimately transitioned to comfort care.